Manajemen dalam Membentuk Sikap Mandiri Santri di Ponpes El Futhah Patimuan Cilacap - Teti Ratnawulan; Ayi Najmul Hidayat; Mugiarto Mugiarto; Agus Salim Chamidi (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2023)
This study aims to describe and analyze of management in an effort to form students' self-reliant attitudes. The research location is at the Pesantren El Futhah Patimuan Cilacap. Research is qualitative. The results of the study are that (a)there are management arrangements in an effort to form the self-reliant attitude of the students, (b) the implementation is in the program of Pembentukan Sikap kemandirian Santri (PSKS), (c)the PSKS program includes the study of religious, foreign languages, skills and production, and programs social, (d)the orientation of the program is religious self-reliant attitudes, social, business, and communal self-reliant attitudes.